Sustainable Agricultural Practices-Impact on Soil Quality and Plant Health - Monokrousos, Nikolaos; Papatheodorou, Efimia M. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Agricultural practices involving the excessive use of chemical fertilizers and pesticides pose major risks to the environment and to human health. The development and adoption of sustainable ecofriendly agricultural management to preserve and enhance the physical, chemical, and biological properties of soils and improve agroecosystem functions is a challenge for both scientists and farmers. The Special Issue entitled "Sustainable Agricultural Practices-Impact on Soil Quality and Plant Health" is a collection of 10 original contributions addressing the state of the art of sustainable agriculture and its positive impact on soil quality. The content of this Special Issue covers a wide range of topics, including the use of beneﬁcial soil microbes, intercropping, organic farming and its effects on soil bacteria and nutrient stocks, application of plant-based nematicides and zeolite amendments, sustainability in CH4 emissions, and the effect of irrigation, fertilization, and environmental conditions as well as land suitability on crop production.